(untitled) (African Journal of Biomedical Research, 2019)
Malaria tolerance is a defence strategy that limits the damage caused by Plasmodium species irrespective of pathogen burden. The mechanisms responsible for this, responses of these mechanisms and their impact on organs to treatment have not been extensively studied. Thus, in this study, serum levels of selected pro- and anti-inflammatory markers, liver and kidney function indices with leucocytes indices in 100 children (1-10 years) with severe falciparum malaria were determined before treatment, at 48 hours during treatment and 48 hours after treatment with WHO recommended dosage of artesunate/artemether-lumefantrine combination therapy using standard methods. Data were analysed using SPSS, differences were considered significant at p<0.05. The results revealed that the serum levels of interleukin-12 (IL-12), interleukin-4 (IL-4), tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ), C-reactive protein (CRP), nitric oxide (NO), creatinine, albumin, total protein and conjugated bilirubin were not significantly changed at higher parasite densities before treatment. Only serum IL-4, CRP, total bilirubin, urea and creatinine levels and alanine aminotransferase activity were significantly reduced below the ranges of those with severe malaria. The results suggest a self-protective feed-back control, indicating tolerance, which reduced the adverse effects of the disease on kidney and liver functions at higher parasite densities. The results also suggest serum IL-12, IL-4, TNF-α, IFN-γ, CRP and NO levels as immune-protective markers for tolerance and serum IL-4 level as an effective marker for disease severity and recovery from the disease in children with severe malaria